Cloning, Expression, and Antitumor Activity of Recombinant Protein of Curcin - Luo, M. J.; Liu, W. X.; Yang, X. Y.; Xu, Y.; Yan, F.; Huang, P.; Chen, F. (Russian in Fiziologiya Rastenii, 2011)
Curcin, a protein isolated from the seeds of Jatropha curcas can be used as a cell-killing agent. To elaborate the purification methods and investigate the antitumor activity of the recombinant protein, the fragment encoding the mature protein of curcin was inserted into E. coli strain M15 and the recombinant strain was induced to express by the optimum inducer (0.5 mM isopropyl-β-D-thiogalactopyranoside). The recombinant protein was expressed in the form of the inclusion body and was purified by Ni-NTA affinity chromatography. The protein of interest was incubated with the tumor cells at various concentrations for different time. It was shown that the target protein could inhibit the growth of NCL-H446, SGC-7901, and S180 at a very low concentration.